Co-Creation in Higher Education: A Systematic Review of the Missed Opportunity for Educator Development - Hajdin, Goran; Balaban, Igor; Matus, Marko (Journal of University Teaching and Learning Practice, 2026)
Student–staff co‑creation, particularly involving the development of e-learning materials and digital environments, is increasingly recognised as a driver of student engagement, curriculum relevance, and professional development in higher education. Parallel to this trend, the Digital Competence of Educators (DigCompEdu) framework has become the reference point for describing and assessing teachers’ technology‑related capabilities. Building on earlier work, this systematic review synthesises 29 peer-reviewed publications published between January 2018 and March 2025 that intersect technology-enhanced student co-creation and educator digital competence. Employing a methodological three‑phase coding protocol adapted from Rienties et al. (2023) and a double‑coder reliability of κ = 0.87, we map how co‑creation initiatives relate to DigCompEdu areas, identify three recurrent engagement archetypes (DigCompEdu‑Light, Project/Hands‑On, and Full DigCompEdu), and expose persistent measurement gaps. Results indicate that technology‑supported co‑creation is most effective when educators operate at least at the DigCompEdu Integrator level and when co-creation designs deliberately cultivate community, collaboration, and cohesion. The discussion highlights methodological deficits and regional imbalances, while practical recommendations emphasise validated measurement and inclusive capacity building.